Approaches and comments on cross-border corporate reorganizations: Mergers and re-domiciliation - Véliz Ortíz, Samuel Jair (2022)
The aim of this paper is to analyse the so-called cross-border corporate reorganisations, which have the particularity of involving companies incorporated and existing in different countries, focusing on mergers and the redomiciliation of companies.To this end, the authors analyse the legal concepts of nationality and domicile of legal entities, mergers and redomiciliation of companies, the considerations that lead to the implementation of this type of operations and, finally, whether it is possible to carry out a cross-border merger and redomiciliation of a Peruvian company abroad according to the current regulations.